Influence of added water and fly ash content on the characteristics, properties and early-age cracking sensitivity of alkali-activated slag/fly ash concrete cured at ambient temperature. (20th May 2018) - Rodrigue, Alexandre; Duchesne, Josée; Fournier, Benoit; Bissonnette, Benoit
Highlights: Increasing added water dosages from 48 to 64 kg/m 3 resulted in increasing both values of absorption after immersion values and volume of permeable voids in the tested alkali-activated concretes. Increasing fly ash content from 20 to 30% of total precursor content resulted in a significant increase of absorption after immersion and volume of permeable voids, no significant effect was observed when increasing further the fly ash content to 40% of total precursor content. Increasing added water dosages from 48 to 64 kg/m 3 did not affect significantly the air void system whereas increasing the fly ash content resulted in increasing air volumes and larger air voids on average, yet overall similar spacing factors. Increasing the added water dosage from 48 to 56 kg/m 3 did not affect significantly the elastic modulus; however, increasing it further to 64 kg/m 3 resulted in a reduction of the order of 10%. Increasing either the added water dosage or fly ash content resulted in lower amounts of cracks in the tested alkali-activated concrete mixtures, and, at the same time, in reduced autogenous volume changes in the corresponding alkali-activated paste mixtures; this strongly suggests that shrinkage is an important contributing factor in the early cracking occurring in the investigates alkali-activated systems. Abstract: For an appropriate air void system, good mechanical properties and low porosity/microcracking in alkali-activated binder systems, appropriate slag/fly ash proportioning, water and admixture contents are needed. Air entraining admixture dosages of up to 10 times the recommended dosage were necessary to obtain minimal air void properties similar to what is needed for normal portland cement concretes subjected to freezing conditions. Increasing added water resulted in increasing absorption and decreasing crack counts in concrete. Increasing fly ash contents resulted in increasing absorption and decreasing early-age crack counts. Increasing both added water and fly ash content resulted in less autogenous shrinkage.